Taken for English [large type] - Newport, Olivia (Newport, Olivia. Valley of choice, 2014)
Family history clearly shows it's never been easy living a plain life in the English world. Will the changes and challenges Annie now faces as a young Amish woman test her newfound faith in good ways or bad?--[p.4] of cover.